1998
DOI: 10.1088/0029-5515/38/12/312
|View full text |Cite
|
Sign up to set email alerts
|

A model for electron transport barriers in tokamaks, tested against experimental data from RTP

Abstract: Recent experiments in the RTP tokamak have shown that the electron temperature, Te, profile in EC heated L mode discharges can have only a small number of distinct profile shapes, depending on the location of the additional heating. The sharp transitions between the profile shapes are associated with the loss or gain of a low rational q surface. These observations suggest that the electron thermal diffusivity χe is a direct function of the safety factor q, with alternating layers of low and high χe. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 32 publications
10
103
2
Order By: Relevance
“…This finding can in turn be helpful to build transport models like the q-comb model [23], [24]. From experimental considerations, such models define indeed barriers are localized around main rational q-values, but the width if the barriers has still to be defined.…”
Section: Experimental Localization Of Barriers In the Tokamak Q -Profilementioning
confidence: 99%
“…This finding can in turn be helpful to build transport models like the q-comb model [23], [24]. From experimental considerations, such models define indeed barriers are localized around main rational q-values, but the width if the barriers has still to be defined.…”
Section: Experimental Localization Of Barriers In the Tokamak Q -Profilementioning
confidence: 99%
“…Those sharp transitions corresponded to changes in the q profile, where q min jumped across a low-order rational value, eg 1, 4/3, 3/2, 2, 5/2, and 3. This indicated that χ e was a direct function of q, with transport barriers occurring near low-order rational values of q and with high values of χ e elsewhere [96,97]. Five medium density discharges representative of the main T e profile levels, from q min < 1 to q min > 3, are included in PR08 (shots #97052248, #97052263, #97052261, #97053056 and #97052270).…”
Section: Rtpmentioning
confidence: 99%
“…At present several possible mechanisms, like an ExB flow shear, a zonal flow, or a magnetic shear, have been proposed. One of these issues is the role of low-order magnetic surfaces in the formation transport barriers which have been discussed in a number of works [12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%